Study guides

☆☆

Q: -4x2 plus 6x plus 40 equals 0?

Write your answer...

Submit

Still have questions?

Related questions

x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

10

6x-52 = 4x+40 6x-4x = 40+52 2x = 92 Answer: x = 46

4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x4x2 + 5x + 1 - 4x2 - 6x = - x + 1 or 1 - x

This is how I did it:8x3+4x2+6x+3[8x3+4x2]+[6x+3][(4x2)(2x+1)]+[(3)(2x+1)]....as you can see, this is in the general form of ab+cb, which factored is b(a+c), so:(2x+1)(4x2+3)

4x2 - 3x - 9

6x = 32 - 4y and 4y - 8 = 6x so 32 - 4y = 4y - 8 ie 40 = 8y so y = 5 and x = 2

2(x + 1)(2x + 1)

x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10

40=4-6x 40-(4)=4-6x-(4) 36=-6x -6=x

5x2-2x+16=4x2+6x ,or x2-8x+16=0, or x2-2(x)(4)+(4)2=0, or (x-4)2=0, or (x-4)(x-4)=0, or x=4

People also asked